Ask Question
25 February, 04:39

Let f (x) = - 3x - 4 and g (x) = 2x - 6. Find (f * g) (-7)

A. - 20

B. 56

C. 28

D. 17

+1
Answers (1)
  1. 25 February, 05:02
    0
    Answer: B: 56

    Step-by-step explanation: First find f (g (x)). Where f (x) = - 3x-4 and

    g (x) = 2x-6. Replace X in f (x) with the equation for g (x)

    f (g (x)) = - 3 (2x-6) - 4. Then use the foil method and simplify.

    = - 6x+18-4

    =-6x+14

    Now sub. in the value of x with - 7 and evaluate.

    =-6 (-7) + 14

    =42+14

    =56
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Let f (x) = - 3x - 4 and g (x) = 2x - 6. Find (f * g) (-7) A. - 20 B. 56 C. 28 D. 17 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers